The landscape design in online education programs based on interactive technologies - Qiao, Shubei; Larionova, Nina; Kamarova, Nagbdu; Grigoriev, Alexander (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to identify the problems that landscape design students face when using Zoom as an educational platform for distance learning purposes and determine their level of satisfaction with distance learning. The main research method was a Likert-scale survey used to assess students’ satisfaction with distance learning. The sample included 90 full-time students enrolled in the garden and landscape construction program. According to the students, the main difficulties in distance learning were systemic errors during the use of the platform. The results can help develop a set of measures to solve and alleviate the identified problems in the future. The findings will enhance the optimization of distance education in general. Future research can focus on the advantages and disadvantages of online educational platforms and explore how user-friendly they are for both students and faculty. Studies can also describe faculty barriers to quality online education and provide suggestions to create a comfortable learning experience for landscape students.